Direct fibre simulation of carbon nanofibres suspensions in a newtonian fluid under simple shear - Yamato, Masayuki (2010)
This work studies the effect of simple shear flows on the dispersion of carbon nanofibres (CNF) in a low viscosity Newtonian matrix. Analysis was performed by using a direct fibre simulation based on Particle Simulation Method (PSM) especially focusing on structure changes under shear flows. Suspensions of CNF/epoxy of different concentrations varying from 0.1 to 3.0 wt% were prepared by simple hand-mixing the as-received fibres with the epoxy resin. These suspensions were then subjected to different flow conditions (shear rates and strains) and their rheological behaviour was characterised. It is demonstrated that simulation can reproduce shear-thinning and structure developments induced by shear flow at different shear rates. Especially at low shear rates, flow induced helical bands were predicted by simulation, which was observed in experiments performed by other researchers and reported in the literature. From the results obtained it is concluded that the direct fibre simulator is a useful tool to design nano-scale fibre composites, allowing for optimisation of the critical parameters to determine the most adequate conditions leading to the required level of fibre dispersion. (C) 2010 Elsevier Inc. All rights reserved.